Development and validation of the FrBio, an international French adaptation of the AzBio sentence lists. (3rd August 2019) - Bergeron, François; Berland, Aurore; Fitzpatrick, Elizabeth M.; Vincent, Christophe; Giasson, Annie; Leung Kam, Kevin; Chafiq, Walid; Fanouillère, Thibaut; Demers, Dominique
Abstract: Objectives: The goal of this work was to develop and normalise an international French version of the AzBio sentence test. Design: A corpus of 1000 sentences was generated. These sentences were recorded with four talkers and processed through a four-channel cochlear implant simulation. The mean intelligibility for each sentence achieved by 16 normal-hearing listeners was computed. The consecutively ordered 165 sentences from each talker rendering an average score of 85% were sequentially assigned to 33 lists of 20 sentences. All lists were presented to 30 normal-hearing and 25 hearing-impaired listeners in order to verify their equivalency. Thirty normal-hearing adults were also recruited to assess the test's psychometrics and define norms. Results: The results of the list equivalency validation study showed no significant differences in percent correct scores for 30 sentence lists. A binomial distribution model was used to estimate the 95% critical differences for each potential percentage score. Normalization data showed an average performance between 96% and 99% with a very low standard deviation. Conclusions: With a set of 30 lists, researchers and clinicians can use the FrBio to evaluate a large number of experimental conditions; changes in performance over time or across conditions can then be tracked.